A tragédia moderna em The Demolition Downtown e Some Problems for the Moose Lodge, de Tennessee Williams - Arnaut de Toledo, Luis Marcio (2022)
This work analyzes elements of modern tragedy, according to Raymond Williams´ concept, in the one-act plays The Demolition Downtown and Some Problems for the Moose Lodge, by Tennessee Williams. The investigation takes into account that the American society and the capitalist system are the tragedy itself, figuring its boundaries in the human field. For this reason, they cause suffering, guilt, ruptures, and social failures. Parodic and satirical elements are identified to intensify the tragedy, in turn, allowing reflection to emerge through laughter and, thus, Williams’ text takes on an unprecedented epic dimension. The playwright’s view of American society deconstructs the stereotypes that structure it, especially stratified issues of their ideologies: the American Way of Life and the American Dream.